Systematic review of pressurized intraperitoneal aerosol chemotherapy for the treatment of advanced peritoneal carcinomatosis. Issue 6 (13th April 2017) - Grass, F; Vuagniaux, A; Teixeira-Farinha, H; Lehmann, K; Demartines, N; Hübner, M
Abstract: Background: Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is a minimally invasive approach under investigation as a novel treatment for patients with peritoneal carcinomatosis of various origins. The aim was to review the available evidence on mechanisms, clinical effects and risks. Methods: This was a systematic review of the literature on pressurized intraperitoneal chemotherapy published between January 2000 and October 2016. All types of scientific report were included. Results: Twenty-nine relevant papers were identified; 16 were preclinical studies and 13 were clinical reports. The overall quality of the clinical studies was modest; five studies were prospective and there was no randomized trial. Preclinical data suggested better distribution and higher tissue concentrations of chemotherapy agents in PIPAC compared with conventional intraperitoneal chemotherapy by lavage. Regarding technical feasibility, laparoscopic access and repeatability rates were 83–100 and 38–82 per cent. Surgery-related complications occurred in up to 12 per cent. Postoperative morbidity was low (Common Terminology Criteria for Adverse Events grade 3–5 events reported in 0–37 per cent), and hospital stay was about 3 days. No negative impact on quality of life was reported. Histological response rates for therapy-resistant carcinomatosis of ovarian, colorectal and gastric origin were 62–88, 71–86 and 70–100 per cent respectively. Conclusion: PIPAC is feasible, safe and well tolerated. Preliminary good response rates call for prospective analysis of oncological efficacy. Abstract : Shows promise